1987
DOI: 10.1002/chin.198746173
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of Azetidin‐3‐ones. Structure of N‐Tosyl‐2‐ethylazetidin‐3one.

Abstract: A general method for the preparation of arylsulfonylazetidinones (II) from the diazo ketones (I) is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…In addition, the equilibrium geometries predicted for the tested azetidines by the MP (ranging from 12º to 17º) is in agreement with the experimental angle of 15º found for a related compound such as 1-toluenesulfonyl-2-ethylazetidine-3-one [20]. Therefore, taking as reference this compound, it is possible to establish that the MP2 approach offers the most appropriate description of the energy and geometry of the studied four-membered heterocycles compared to the DFT, HF and semi-empirical methods used, which is significantly important for the prediction of the linear and nonlinear properties.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, the equilibrium geometries predicted for the tested azetidines by the MP (ranging from 12º to 17º) is in agreement with the experimental angle of 15º found for a related compound such as 1-toluenesulfonyl-2-ethylazetidine-3-one [20]. Therefore, taking as reference this compound, it is possible to establish that the MP2 approach offers the most appropriate description of the energy and geometry of the studied four-membered heterocycles compared to the DFT, HF and semi-empirical methods used, which is significantly important for the prediction of the linear and nonlinear properties.…”
Section: Resultssupporting
confidence: 80%
“…For heterocycles such as azetidine-3-one, oxetane-3-one and thietane-3-one, some experimental parameters related with geometry and thermodynamic properties have been reported [18][19][20]. Recently, conformational studies and thermodynamic properties have been theoretically calculated for a series of azetidines, oxetanes, phosphetanes and thietanes functionalised with a double bond at position 3 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) (Figures 2 and 3) using mPW1B95 approach [21]; however, there is little theoretical and experimental information available for these classes of four-membered heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…The absolute values of distant coupling constants ( 4 J ) in 1 H NMR spectra, which are rather large, provide the evidence of this fact. Thus, in 2-methyl-, 2-ethyl-, and 2-benzyl-1-tosylazetidin-3-ones 6 , 4 J trans values were of 2.70, 3.63, and 4.05 Hz, respectively ).…”
Section: A Structural Datamentioning
confidence: 87%
“…The four-membered azetidin-3-one ring has a nonplanar structure. The first X-ray investigation was carried out on 1- p -toluenesulfonyl-2-ethylazetidin-3-one 4 (Figure ) . It was shown that the deviation of the nitrogen atom from the plane of the three-ring carbon atoms is 0.35 Å, and the inflection of the ring along the C−C line is 15°.…”
Section: A Structural Datamentioning
confidence: 99%
See 1 more Smart Citation